Uterine balloon tamponade as an adjunct to misoprostol for the treatment of uncontrolled postpartum haemorrhage: a randomised controlled trial in Benin and Mali - DUMONT, ALEXANDRE; BODIN, CECILE; HOUNKPATIN, BENJAMIN IGNACE BODOUNRIN; POPOWSKI, THOMAS; TRAORE, MAMADOU; PERRIN, RENÉ-XAVIER (My University, 2017)
Objective To assess the effectiveness of low-cost uterine tamponade as an adjunct to misoprostol for the treatment of uncontrolled postpartum haemorrhage (PPH) in lowresource settings. Design Randomised controlled trial. Setting Seven healthcare facilities in Cotonou, Benin and Bamako, Mali. Population Women delivering vaginally who had clinically diagnosed PPH that was suspected to be due to uterine atony, who were unresponsive to oxytocin and who needed additional uterotonics. Methods Women were randomly assigned to receive uterine balloon tamponade with a condom-catheter device or no tamponade; both groups were also given intrarectal or sublingual misoprostol. Main outcome measure Proportion of women with invasive surgery or who died before hospital discharge. Results The proportion of primary composite outcome did not differ significantly between the tamponade arm (16%; 9/57) and the standard second line treatment arm (7%; 4/59): relative risk 2.33 (95% CI 0.76 to 7.14, p=0.238). A significantly increased proportion of women with tamponade and misoprostol versus misoprostol alone had total blood loss more than 1000 mL: relative risk 1.52 (95% CI 1.15 to 2.00, p=0.01). Case fatality rate was higher in the tamponade group (10%; 6/57) than in the control group (2%; 1/59) (p=0.059).
Keywords: Uterine balloon tamponade; misoprostol postpartum haemorrhage